Cost-effectiveness of vitamin D supplementation and exercise in preventing injurious falls among older home-dwelling women: findings from an RCT. Issue 1 (January 2016) - Patil, R.; Kolu, P.; Raitanen, J.; Valvanne, J.; Kannus, P.; Karinkanta, S.; Sievänen, H.; Uusi-Rasi, K.
Abstract Summary This study assessed the cost-effectiveness of vitamin D supplementation and exercise, separately and combined, in preventing medically attended injurious falls among older home-dwelling Finnish women. Given a willingness to pay of €3000 per injurious fall prevented, the exercise intervention had an 86 % probability of being cost-effective in this population. Introduction The costs of falling in older persons are high, both to the individual and to society. Both vitamin D and exercise have been suggested to reduce the risk of falls. This study assessed the cost-effectiveness of vitamin D supplementation and exercise, separately and combined, in preventing medically attended injurious falls among older Finnish women. Methods Economic evaluation was based on the results of a previously published 2-year randomized controlled trial (RCT) where 409 community-dwelling women aged 70 to 80 years were recruited into four groups: (1) no exercise + placebo (D−Ex−), (2) no exercise + vitamin D 800 IU/day (D+Ex−), (3) exercise + placebo (D−Ex+), and (4) exercise + vitamin D 800 IU/day (D+Ex+). The outcomes were medically attended injurious falls and fall-related health care utilization costs over the intervention period, the latter evaluated from a societal perspective based on 2011 unit costs. Incremental cost-effectiveness ratios (ICER) were calculated for the number of injurious falls per person-year prevented and uncertainty estimated using bootstrapping. Results Incidence rate ratios (95 % CI) for medically attended injurious falls were lower in both Ex+ groups compared with D−Ex−: 0.46 (0.22 to 0.95) for D−Ex+, 0.38 (0.17 to 0.81) for D+Ex+. Step-wise calculation of ICERs resulted in exclusion of D+Ex− as more expensive and less effective. Recalculated ICERs were €221 for D−Ex−, €708 for D−Ex+, and €3820 for D+Ex+; bootstrapping indicated 93 % probability that each injurious fall avoided by D−Ex+ per person year costs €708. At a willingness to pay €3000 per injurious fall prevented, there was an 85.6 % chance of the exercise intervention being cost-effective in this population. Conclusions Exercise was effective in reducing fall-related injuries among community-dwelling older women at a moderate cost. Vitamin D supplementation had marginal additional benefit. The results provide a firm basis for initiating feasible and cost-effective exercise interventions in this population.